SISTEM INFORMASI MANAJEMEN PELAYANAN PERIZINAN SATU PINTU (SIMTU) KABUPATEN OGAN KOMERING ILIR - Mirza, Ahmad Haidar (Universitas Bina Darma, 2012)
Licensing Agency and Investment Komering Ogan Ilir district has a duty and a great authority in the field of licensing and non-licensing. Increase in duties, responsibilities and authority should be accompanied by an increase in supporting infrastructure and facilities so that Licensing Agency and Investment Ogan Ilir Komering can enhance optimal service to the community. To achieve excellent public services to the community, developed One Stop Service Information System (SIMTU) with the application of information technology as the spearhead of the public service. One Stop Service Information System (SIMTU) Komering Ogan Ilir (OKI) which was developed consisting of three points of service, namely back office, front office and information kiosks. Keywords: Technology, Licensing, Information Systems, One Stop Service